The acceleration of metastases after tumor removal and the paradoxical phenomenon of concomitant tumor resistance - Montagna, Daniela Romina (2018)
Although surgical extirpation of tumors is usually clinically recommended, tumor removal may entail an undesired side effect: the risk of accelerating the growth of metastases. This effect may account for the relatively modest survival benefits observed when surgery is accomplished after tumor cells have already disseminated to distant anatomical sites even when tumor removal is combined with chemotherapy or immunotherapy. Although different mechanisms could contribute to the enhancement of residual tumor growth after tumor removal, probably a main effect is associated with the withdrawing of an inhibitory effect generated, by certain circumstances, by the primary tumor on its own metastases. This inhibitory effect is a particular case of a more general and paradoxical phenomenon known as concomitant tumor resistance (CR) in which a tumor-bearing host inhibits or retards the growth of secondary tumor implants despite the fact that the primary tumor grows progressively. In this essay we especially focus on the last investigations of our laboratory concerningthe importance of tyrosine isomers as mediators of the phenomenon of CR and on their capacity to inhibit established metastases. Taking into account that metastases are considered the main problem in cancer pathology, our investigations aimed to elucidate the molecular basis of the phenomenon of CR might stimulate the design of new and less harmful means of managing malignant diseases, especially by controlling the growth of metastases after the removal of a primary tumor, or after other injuries or stressors that have been claimed to promote the escape of metastases from dormancy.